Sensitivity to the Focusing Significance of the Gaze Direction of the Partner at Mentally Retarded Preschoolers - Яна К. Смирнова (Rossijskij psihologičeskij žurnal., 2019)
Introduction. The relevance of the study of communication between the mechanism of joint attention and the subsequent normal and abnormal development of the child has been substantiated. It has been shown that a child’s ability to initiate and react to a joint attention of an ontogenetically precedes emergence of social and cognitive abilities. It has been determined a role of the joint attention in the child's ability o integrate information on himself, on other person and ability to unite his own intentions and other person's intentions. The problem of need for solution to a question of how the cognitive development pf the child interferes with development of social experience of the child has been raised. Methods. Sample group was made by 514 children of preschool age, including the children with developmental disorders which characteristic of different forms of mental retardation. In the section there are descriptions of some techniques: 1. “Wrong opinion test”, “Sally-Ann”; the task “What does Charlie want?”, etc. for assessment of children's understanding of intentions, desires, the interests of others according to behavioural manifestations. 2. The developed task for assessment of ability of using the gaze direction of the character on the picture for the purpose of determination of its intentions. 3. Neuropsychological tests for a research of the block of reception and processing of information. Results. Potential mechanisms of integration disorder of the joint attention, decrease in recognition of the focusing value of the gaze are revealed. The variability of formation and age changes of joint attention skills, to be exact, existence of differences in recognition, synthesis and interpretation of the focusing social information proceeding from eye contact is shown. It is revealed that children with a developmental delay have a low level of the "descending" joint attention. The parallelism of early deficiency of joint attention and difficulties of processing of information is revealed. Discussion. The data display synchronism of cognitive development and formation of the mechanism of the joint attention. The conclusion is drawn that difficulties of integrative function of processing of social information can be combined with difficulties of synthesis of separate information signs in a Gestalt, complex information fusion, subject and symbolical orientation in space.